Calcium Nutrition in Fig Orchards Enhance Fruit Quality at Harvest and Storage - Souza, Jackson Mirellys Azevêdo; Leonel, Sarita [UNESP]; Leonel, Magali [UNESP]; Garcia, Emerson Loli [UNESP]; Ribeiro, Luiza Rocha [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Martins, Rafaelly Calsavara [UNESP]; de Souza Silva, Marcelo; Monteiro, Laís Naiara Honorato [UNESP]; Duarte, Anita Santos [UNESP] (MDPI, 2023)
Due to the high perishability of figs, calcium stands out as an important nutrient for orchard management. This study aims to study the pre-harvest applications of calcium chloride in fig orchards. The fig trees were sprayed with 0, 0.5, 1.0, 1.5 and 2.0% CaCl2, and fruits were thereafter stored for 0, 7, 14 and 21 d. The variables analysed were the concentration of calcium in leaves and fruits, weight loss, fruit decay, pectinolytic enzyme activity, and physical and chemical attributes of the fruits; CaCl2 sprays enhanced fruit Ca2+ concentration in leaves (14.03%) and fruits (29.3%) and were effective in reducing polygalacturonase and pectin methylesterase activity, weight loss and fruit decay. Pre-treatment with 1% CaCl2 provided fruits with larger diameters, greater firmness, and higher levels of total phenolic compounds in both fruit peel and pulp. The pre-harvest application at 1% CaCl2 showed to be a promising technique in producing high quality fruits and extended storage by approximately 7 to 10 days. These findings may be useful in planning new cultural practices for fig orchards that produce high-quality fruit with desirable characteristics for growers and consumers.
Keywords: Ficus caricaL; fruit decay; pectin methylesterase; polygalacturonase; weight loss